2017
DOI: 10.14302/issn.2326-0793.jpgr-17-1571
|View full text |Cite
|
Sign up to set email alerts
|

Shotgun Label-Free Proteomic Analyses of the Oyster Parasite Perkinsusmarinus

Abstract: Perkinsus marinus is an intracellular parasitic protozoan that is responsible for serious disease epizootics in marine bivalve molluscs worldwide. Despite all available information on P. marinus genomics, more baseline data is required at the proteomic level. Our aim was to study the proteome profile of in vitro cultured P. marinus isolated from oysters Crassostrea spp. using a label-free shotgun UDMS E approach. A total of 4073 non redundant proteins were identified across three biological replicates with str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…However, tetra-polyploidy pose a significant bottleneck for the assembly (El-Sayed et al, 2007;Bogema et al, 2020). Proteome studies identified that P. marinus possess 4,073 non-redundant hypothetical proteins, of which 36 and 27% are involved in metabolic and cellular processes, respectively (Marcia et al, 2017). Additionally, the rhoptry proteins such as serine-threonine kinases, protein phosphatases, proteosomes, and a virulent candidate merozoite surface protein 3, which are known to play a crucial role in parasite invasion and cell-cell communication during the invasion in P. falciparum were also identified in P. marinus.…”
Section: Discussionmentioning
confidence: 99%
“…However, tetra-polyploidy pose a significant bottleneck for the assembly (El-Sayed et al, 2007;Bogema et al, 2020). Proteome studies identified that P. marinus possess 4,073 non-redundant hypothetical proteins, of which 36 and 27% are involved in metabolic and cellular processes, respectively (Marcia et al, 2017). Additionally, the rhoptry proteins such as serine-threonine kinases, protein phosphatases, proteosomes, and a virulent candidate merozoite surface protein 3, which are known to play a crucial role in parasite invasion and cell-cell communication during the invasion in P. falciparum were also identified in P. marinus.…”
Section: Discussionmentioning
confidence: 99%